Analysis of Entrepreneurial Interest of Mathematics Education Students: A Study at Higher Education - Hariaty Hamid; Nurmala R; Nur Afni Oktavia (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Mapping the entrepreneurial intention of pre-service exact science teachers is crucial for understanding graduate readiness in competitive job markets, particularly within the unique socio-economic context of border regions. This study analyzes the level of entrepreneurial intention among Mathematics Education students at Universitas Borneo Tarakan (UBT) and identifies its key drivers and barriers. Employing a quantitative descriptive-exploratory design, primary data were gathered from 53 active students via a validated questionnaire. The empirical results demonstrate a high level of entrepreneurial intention (Grand Mean = 3.72 on a 1–5 scale). The absolute majority (70%) fell into the high-interest category, with 15% already managing active businesses. The primary internal drivers had a very high positive attitude (4.10) and robust self-efficacy (3.85), which translated into a strong preference for "edupreneurship" ventures like independent tutoring centers and digital learning content development. Conversely, a critical psychological bottleneck was identified in risk management; the courage to take risks scored the lowest (3.25, medium category) due to capital anxiety and a highly calculative mathematical mindset. However, environmental influences (subjective norms) served as a strong counterweight (3.68). To bridge the intention-action gap, university policymakers must reform the curriculum by integrating practical business simulations and financial risk mitigation to foster regional economic resilience.